Relationship of Nutritional Status, Nutrient Intake, Physical Activity, and Smoking Habits with Hypertension in Cardiology Outpatient Clinic - Nur Salsabila; Lili Amaliah; Ratu Diah Koerniawati (Media Publikasi Cendekia Indonesia, 2025)
This study aims to investigate the relationship between nutritional status, nutrient intake (including fat, fiber, and sodium), physical activity, and smoking habits, and the incidence of hypertension at the Cardiac Polyclinic of RSUD Banten. This study was conducted from January to February, utilizing a quantitative method with a cross-sectional design and a purposive sampling technique, involving 36 respondents. Research data were collected through direct interviews using the SQ-FFQ, IPAQ SF, and GN-SBQ questionnaires. The results showed that the majority of respondents (52.8%) in the Cardiac Polyclinic of RSUD Banten were female, aged 50–64 years, and had a family history of hypertension (63.9%). Most respondents (91.7%) experienced hypertension, with half of the respondents having excess nutritional status. Additionally, excessive fat intake (72.2%), low fiber intake (61.1%), and excessive sodium intake (27.8%) were found. A total of 44.4% of respondents had low physical activity, and 11.1% had a very heavy smoking habit. Based on the analysis using the Chi-square test, it was found that there were significant relationships between nutritional status (p=0.001), fat intake (p=0.021), physical activity (p=0.043), and smoking habits (p=0.020) with the incidence of hypertension, while there were no significant relationships between fiber intake (p=0.353) and sodium intake (p=0.529) with the incidence of hypertension. The conclusion of this study is that nutritional status, fat consumption, physical activity, and smoking habits are associated with the incidence of hypertension in outpatients at the Cardiac Polyclinic of RSUD Banten